Integration of subcellular partitioning and chemical forms to understand silver nanoparticles toxicity to lettuce (Lactuca sativa L.) under different exposure pathways. (November 2020) - Li, Wei-Qi; Qing, Ting; Li, Cheng-Cheng; Li, Feng; Ge, Fei; Fei, Jun-Jie; Peijnenburg, Willie J.G.M.
Abstract: The current understanding of the biological impacts of silver nanoparticles (AgNPs) is restricted to the direct interactions of the particles with biota. Very little is known about their intracellular fate and subsequent toxic consequences. In this research we investigated the uptake, internal fate (i, e., Ag subcellular partitioning and chemical forms), and phytotoxicity of AgNPs in lettuce following foliar versus root exposure. At the same AgNP exposure concentrations, root exposure led to more deleterious effects than foliar exposure as evidenced by a larger extent of reduced plant biomass, elevated oxidative damage, as well as a higher amount of ultrastructural injuries, despite foliar exposure leading to 2.6–7.6 times more Ag bioaccumulation. Both Ag subcellular partitioning and chemical forms present within the plant appeared to elucidate this difference in toxicity. Following foliar exposure, high Ag in biologically detoxified metals pool (29.2–53.0% by foliar exposure vs. 12.8–45.4% by root exposure) and low Ag proportion in inorganic form (6.1–11.9% vs. 14.1–19.8%) potentially associated with AgNPs tolerance. Silver-containing NPs (24.8–38.6 nm, 1.5–2.3 times larger than the initial size) were detected in lettuce plants exposed to NPs and to dissolved Ag +, suggesting possible transformation and/or aggregation of AgNPs in the plants. Our observations show that the exposure pathway significantly affects the uptake and internal fate of AgNPs, and thus the associated phytotoxicity. The results are an important contribution to improve risk assessment of NPs, and will be critical to ensure food security. Graphical abstract: Image 1 Highlights: This is the first study on subcellular and chemical forms partitioning of AgNPs in planta under different exposure pathway. Lettuce has higher tolerance to AgNP following foliar exposure than via root exposure. AgNP sequestration in metal-rich granules and heat stable fractions could best explain the AgNP tolerance. Low Ag proportion in inorganic form was potentially associated with AgNPs tolerance. Silver-containing NPs of 23.7–39.4 nm were detected in planta by spICP-MS analysis.